Dynamics of Implementation of Halal Certification for Business Actors - Fitriani, Aprilya; Alwi, Muhammad Muhib; Dawud, Mochammad; Fanani, Zainul (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
The mandatory 2024 halal certification for business actors is a must. From an economic aspect, products labeled halal can compete and be marketed more broadly. However, in reality, many problems are encountered in implementing halal certification. The problem that arises is the guarantee of the supply of halal materials in the halal supply chain for materials used by micro, small, and medium enterprises (MSMEs). Furthermore, the human resource capacity of halal guarantors is limited, and awareness of participating in halal certification still needs to improve. This study uses a literature review approach to analyze the phenomenon of implementing halal certification for business actors. Problems that arise in halal certification application can be studied using various scientific aspects, namely quality management, awareness of business actors, and interpersonal communication to halal by design innovation. This research is limited to the perspective of business actors, so further research is needed that integrates the perspectives of the government, business actors, and consumers.